2004
DOI: 10.1530/eje.0.1510277
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil improves diabetes and rat islet beta-cell damage induced by streptozotocin in vivo and in vitro

Abstract: Objective: N-(2-hydroxyethyl)-nicotinamide nitrate (nicorandil) is a unique anti-anginal agent, reported to act as both an ATP-sensitive K þ channel opener (PCO) and a nitric oxide donor. It also has an anti-oxidant action. We examined the effects of nicorandil on streptozotocin (STZ)-induced islet b-cell damage both in vivo and in vitro. Design and methods: STZ-induced diabetic Brown Norway rats (STZ-DM) were fed with nicorandil-containing chow from day 2 (STZ-DM-N48), 3 (STZ-DM-N72), and 4 (STZ-DM-N96) to da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Several reports have shown the relationship between dysfunction in K ATP channel gating and diabetes [17]. A previous study reported that nicorandil, a mitochondrial K ATP channel opener, protects from diabetes through inhibition of the production of ROS in the streptozotocin-treated rats [52]. More recently, we also observed that the HG reduces a decrease in the cardiac expression of K ATP channels and that opening of K ATP channels protects cardiac cells against the HG-induced injury, including ROS production [7].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown the relationship between dysfunction in K ATP channel gating and diabetes [17]. A previous study reported that nicorandil, a mitochondrial K ATP channel opener, protects from diabetes through inhibition of the production of ROS in the streptozotocin-treated rats [52]. More recently, we also observed that the HG reduces a decrease in the cardiac expression of K ATP channels and that opening of K ATP channels protects cardiac cells against the HG-induced injury, including ROS production [7].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis occurring at the onset of diabetes is considered a major causative factor. The overexpression of anti‐apoptotic proteins has been demonstrated to protect pancreatic β cells exposed to STZ . STZ also induces pancreatic β‐cell apoptosis by the activation of PARP, caspase‐3 and caspase‐9 .…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of anti‐apoptotic proteins has been demonstrated to protect pancreatic β cells exposed to STZ . STZ also induces pancreatic β‐cell apoptosis by the activation of PARP, caspase‐3 and caspase‐9 . The molecular mechanisms underlying apoptosis were divided into two types, one including the initiators (caspase‐2, caspase‐8, caspase‐9, caspase‐10) and effectors or executioners of apoptosis (caspase‐3, caspase‐6, caspase‐7) and the other including members of the anti‐apoptotic BCL‐2 protein family .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human umbilical vein endothelial cells, nicorandil inhibited apoptosis induced by serum starvation by inhibiting ROS production [19]. Furthermore, nicorandil protected from diabetic through inhibition of the production of ROS stimulated by high glucose [20]. Therefore, we hypothesised that nicorandil can prevent diabetic endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%